1999
DOI: 10.1136/bjo.83.3.378
|View full text |Cite
|
Sign up to set email alerts
|

Red-free light in applanation tonometry

Abstract: Red-free light in applanation tonometryEDITOR,-Goldmann's applanation tonometry is generally performed using cobalt blue filter and fluorescein in order to obtain accurate localisation of the apex of the tear meniscus. 2The peak transmission value of the cobalt blue filter BG12 on the Haag-Streit slit lamp 900 BM is 0.80 at 400 nm, whereas that of the red-free filter BG39 is 0.965 at 490 nm. The peak absorption value of fluorescein in dilute aqueous solution at physiological tear pH is also at 490 nm.3 Greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Shaikh and Mars (13) measured the IOP with fluorescein drops using red-free light and compared the results with measurements taken using blue light. The authors found no significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…Shaikh and Mars (13) measured the IOP with fluorescein drops using red-free light and compared the results with measurements taken using blue light. The authors found no significant difference.…”
Section: Discussionmentioning
confidence: 99%